2021
DOI: 10.1007/s00359-021-01506-1
|View full text |Cite
|
Sign up to set email alerts
|

Localisation of cryptochrome 2 in the avian retina

Abstract: Cryptochromes are photolyase-related blue-light receptors acting as core components of the mammalian circadian clock in the cell nuclei. One or more members of the cryptochrome protein family are also assumed to play a role in avian magnetoreception, but the primary sensory molecule in the retina of migratory birds that mediates light-dependent magnetic compass orientation has still not been identified. The mRNA of cryptochrome 2 (Cry2) has been reported to be located in the cell nuclei of the retina, but Cry2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…Cryptochromes (Cry), currently the only group of vertebrate proteins known to form radical pairs upon photoexcitation (Ritz et al 2000 ; Liedvogel et al 2007 ; Maeda et al 2012 ; Zoltowski et al 2019 ; Xu et al 2021 ), have been proposed as the light-activated, radical-pair-forming, magnetosensory proteins in the avian retina (Ritz et al 2000 ; Mouritsen et al 2004 ; Maeda et al 2012 ; Nießner et al 2014 ; but see Bolte et al 2021 ; Hore and Mouritsen 2016 ; Günther et al 2018 ; Xu et al 2021 ; Wong et al 2021 ). At least six different cryptochrome variants are known to occur in retinal neurons of night-migratory songbirds: Cry1a (Mouritsen et al 2004 ; Möller et al 2004 ; Nießner et al 2011 ; Bolte et al 2021 ), Cry1b (Möller et al 2004 ; Bolte et al 2016 ; Nießner et al 2016 ), Cry2a (Mouritsen et al 2004 ; Möller et al 2004 ; Balay et al 2021 ; Einwich et al 2021 ), Cry2b (Hochstoeger et al 2020 ; Balay et al 2021 ), Cry4a (Liedvogel and Mouritsen 2010 ; Günther et al 2018 ; Wu et al 2020 ; Xu et al 2021 ), and Cry4b (Einwich et al 2020 ); a and b forms are alternative splicing variants.…”
Section: Introductionmentioning
confidence: 99%
“…Cryptochromes (Cry), currently the only group of vertebrate proteins known to form radical pairs upon photoexcitation (Ritz et al 2000 ; Liedvogel et al 2007 ; Maeda et al 2012 ; Zoltowski et al 2019 ; Xu et al 2021 ), have been proposed as the light-activated, radical-pair-forming, magnetosensory proteins in the avian retina (Ritz et al 2000 ; Mouritsen et al 2004 ; Maeda et al 2012 ; Nießner et al 2014 ; but see Bolte et al 2021 ; Hore and Mouritsen 2016 ; Günther et al 2018 ; Xu et al 2021 ; Wong et al 2021 ). At least six different cryptochrome variants are known to occur in retinal neurons of night-migratory songbirds: Cry1a (Mouritsen et al 2004 ; Möller et al 2004 ; Nießner et al 2011 ; Bolte et al 2021 ), Cry1b (Möller et al 2004 ; Bolte et al 2016 ; Nießner et al 2016 ), Cry2a (Mouritsen et al 2004 ; Möller et al 2004 ; Balay et al 2021 ; Einwich et al 2021 ), Cry2b (Hochstoeger et al 2020 ; Balay et al 2021 ), Cry4a (Liedvogel and Mouritsen 2010 ; Günther et al 2018 ; Wu et al 2020 ; Xu et al 2021 ), and Cry4b (Einwich et al 2020 ); a and b forms are alternative splicing variants.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic compass sense of night-migratory birds seems to be based on a light-dependent, radical-pair-based mechanism in cryptochrome proteins [1,2,[26][27][28][29][30][31][32][33][34][35][36][37] located in both of the birds' eyes [38][39][40][41]. Among the six cryptochromes known from bird retinas [15,36,[42][43][44][45][46][47][48][49][50][51], cryptochrome 4 (Cry4) seems particularly interesting because it binds the cofactor flavin, which is crucial for any magnetic sensitivity of any cryptochrome [36,46,[52][53][54]. So far, there is no convincing evidence of flavin binding in other types of vertebrate cryptochomes, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these findings, Mouritsen et al ( 2005 ) proposed that this night-vision processing could be related to a vision-mediated magnetic compass based on radical-pair-forming sensor molecules, cryptochromes, located in the birds eyes (Ritz et al 2000 ; Hore and Mouritsen 2016 ; Mouritsen 2018 , 2021 ). Cryptochromes are currently considered the most likely molecular basis for a radical pair-based magnetic compass sense in birds (Möller et al 2004 ; Mouritsen et al 2004b ; Liedvogel et al 2007b ; Niessner et al 2011 , 2016 ; Bolte et al 2016 , 2021 ; Hore and Mouritsen 2016 ; Günther et al 2018 ; Zoltowski et al 2019 ; Einwich et al 2020 , 2021 ; Xu et al 2021 ). Connectivity studies have shown that the eye and Cluster N are interconnected via parts of the thalamofugal visual pathway (Heyers et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%